1993
DOI: 10.1002/jez.1402660111
|View full text |Cite
|
Sign up to set email alerts
|

Effects of epidermal growth factor, insulin‐like growth factor‐I, and dialyzed porcine follicular fluid on porcine oocyte maturation in vitro

Abstract: Undefined follicular factors that may influence nuclear maturation and/or cytoplasmic maturation are required during in vitro maturation of pig oocytes. Epidermal growth factor (EGF), insulin-like growth factor-I (IGF-I), and dialysed porcine follicular fluid (dpFF) were evaluated for their effects on porcine oocyte nuclear maturation in vitro. In Experiment I, eight different maturation media were made in a split-plot factorial design with dpFF (0% vs. 10% v/v dialyzed pFF) as the whole plot component, and EG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 21 publications
4
46
0
Order By: Relevance
“…Although EGF-R mRNA were not detectable in both oocytes and cumulus cells in this study, ErbB3 transcript was detectable in both oocytes and cumulus cells at all stages of in vitro maturation. Since ErbB3 is a member of EGF-R subfamily of receptor tyrosine kinase and is reported to be a receptor for variety types of EGF agonists [26,27], ErbB3 in oocytes and cumulus cells during in vitro maturation in the present culture system might mediate various responses for EGF agonists detected as mRNA transcripts in porcine COCs [17,18] or those exogenously added to the maturation medium [8,18,28,29] by an autocrine or a paracrine circuit of cumulus cells and/ or oocytes. Three signal transducing transmembrane receptors, which bear significant homology to the EGF-R/ErbB1, are currently known: ErbB2, ErbB3 and ErbB4 [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although EGF-R mRNA were not detectable in both oocytes and cumulus cells in this study, ErbB3 transcript was detectable in both oocytes and cumulus cells at all stages of in vitro maturation. Since ErbB3 is a member of EGF-R subfamily of receptor tyrosine kinase and is reported to be a receptor for variety types of EGF agonists [26,27], ErbB3 in oocytes and cumulus cells during in vitro maturation in the present culture system might mediate various responses for EGF agonists detected as mRNA transcripts in porcine COCs [17,18] or those exogenously added to the maturation medium [8,18,28,29] by an autocrine or a paracrine circuit of cumulus cells and/ or oocytes. Three signal transducing transmembrane receptors, which bear significant homology to the EGF-R/ErbB1, are currently known: ErbB2, ErbB3 and ErbB4 [27].…”
Section: Discussionmentioning
confidence: 99%
“…Only COCs possessing a compact cumulus mass and evenly granulated ooplasm were selected for the experiments. COCs (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) were transferred to a droplet of maturation medium (0.2 ml) under paraffin oil (Nakarai Tesque, Inc., Kyoto, Japan) in a polystyrene dish (35 mm: Becton Dickinson Labware, Oxnard, CA, USA) and cultured at 38.5 C in an atmosphere of 5% CO 2 in air. The maturation medium consisted of 80% (v/v) TLP-PVA modified by deleting penicillin G and streptomycin sulfate and supplementing with 1.0 mM glutamine (Sigma Chemical Co., St Louis, MO, USA), 0.2 mM isoleucine (Sigma), 0.05 mM methionine (Sigma), 0.1 mM phenylalanine (Sigma), 0.57 mM cysteine hydrochloride hydrate (Sigma), 10 i.u.…”
Section: In Vitro Maturation Of Porcine Cocsmentioning
confidence: 99%
“…The variations in the incidence of cumulus cells expansion and nuclear maturation reported by various workers as compared with the present investigation might be due to the variations in species, composition of media, additives, concentration of growth factors used, and period and temperature of incubation of oocytes. Reed et al (1993) reported that the addition of EGF to IVM medium supplemented with gonadotropins significantly stimulated the nuclear maturation of pig oocytes. Coskun and Lin (1993) and Lorenzo et al (1994) observed that exogenous EGF induced oocyte maturation by generating a positive signal in the cumulus cells in pig and cattle respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of exogenous growth factor to the maturation medium results in beneficial effects on porcine oocyte maturation [8][9][10][11][12]. On the other hand, the observation that transcripts for growth factors detected in both oocytes and/or cumulus cells throughout in vitro maturation suggests that various amounts of growth factors would be produced, at least by cumulus cells, and accumulated in the maturation medium during in vitro culture.…”
Section: Discussionmentioning
confidence: 99%
“…First, several growth factors have been shown to be present in follicular fluid [2][3][4]. Second, the addition of exogenous growth factor to the maturation medium resulted in beneficial effects on oocyte maturation in mouse [5], rat [6], cow [7] and pig [8][9][10][11][12]. Third, it has been reported that a number of growth factor ligand and/or receptor mRNA transcripts have been detected within mouse [13,14], bovine [15], ovine [16], human [17][18][19] and porcine oocytes [20,21].…”
mentioning
confidence: 99%